Frequência da raiva em herbívoros e humanos no estado do tocantins de 1999 A 2010: RELATÓRIO TÉCNICO - Oliveira, Monike S.; Frota, Fabrício. P.; Carvalho, Márcio P.; De O. Bersano, Paulo Ricardo [UNESP]; Dias, Francisca Elda F.; Cavalcante, Tânia V.; Santos, H. D.; Minharro, S. (My University, 2013)
Rabies is a fatal zoonotic disease, causing serious economic and public health problems. In Brazil, the economic losses caused by this disease are around 15 million dollars a year. In 2000, of the 6, 300 cases that occurred in Brazil, 2, 641 (41.29%) only in Tocantins, so the aim of this study was to analyze the frequency of rabies in Tocantins over the 2000, by official data published from 1999 to 2010. The data revealed that 80.33% in 1999 and 98.66% in 2000, the frequency of rabies cases in relation to occurring in the northern region of Brazil, decreased to 34.89% in 2001, but continued with the effective participation the frequency of cases occurring in the northern region, with a variation of 21.76% in (2003) to 52.25% (2009), and observed that the cycle of rabies in Tocantins occurred 3 to 4 years, shortly after the outbreak of 2000, in 2002, 2005 and 2009, often more than 45% of cases to the North.
Survey of rabies in herbivores and humans in state of tocantins from 1999 to 2010: Technical report
Keywords: Northern region Brazil; PNCRH; Rabies; Zoonosis